IMPLEMENTASI GAME EDUKASI PENGENALAN KEBUDAYAAN KEPULAUAN RIAU UNTUK ANAK USIA DINI BERBASIS ANDROID - Saputra, Rios; Sunarsan Sitohang (LPPM Universitas Putera Batam, 2024)
ABSTRACT Supporting media in the learning and teaching process is still very lacking, one of which is in the subject of Cultural Arts about regional culture in Indonesia which makes children less motivated and easily bored in learning if they only listen to explanations from teachers and read textbooks. In general, children really like things that are unique in any case, for example in terms of learning, because learning is important to increase childrens’s knowledge. Therefore, researchers want to create an educational game introducing Indonesian culture for children to gerenerasi successor the nation as a learning medium that can increase children's interest in learning to know the culture in Indonesia. The preparation of this game design uses the Game Development Life Cycle (GDLC) method, Unified Modelling Language (UML) to analyze, which consists of Use Case Diagram, Activity Diagram, and Sequence Diagram. Researchers also used Construct2 Software to design the game. This game is played by one player in the form of a Quiz. Where players will answer several questions to achieve the highest score that has been achieved before.